Pengaruh Gaya Kepemimpinan dan Motivasi Terhadap Kinerja Pegawai dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Dinas Pendidikan dan Kebudayaan Kota Padang Panjang - Dani Reka Putra; Vicky Brama Kumbara; Nia Nadilla (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the influence of leadership style and motivation on employee performance, with job satisfaction serving as an intervening variable, at the Department of Education and Culture of Padang Panjang City. The study employs a Structural Equation Modeling (SEM) approach using SmartPLS 3.0 software for analysis. The population and sample consist of employees from the Department of Education and Culture of Padang Panjang City. The results indicate a positive and significant influence of leadership style on job satisfaction and of motivation on job satisfaction. There is a positive but non-significant influence of leadership style on employee performance, whereas motivation has a positive and significant influence on employee performance. Job satisfaction has a positive and significant influence on employee performance. Job satisfaction does not mediate the relationship between leadership style and employee performance, but it does mediate the relationship between motivation and employee performance.